Tool-use induces morphological updating of the body schema - Cardinali, Lucilla; Frassinetti, Francesca; Brozzoli, Claudio; Urquizar, Christian; Roy, Alice C.; Farnè, Alessandro (Current biology, 2009)
To control bodily movements the human brain relies on a somatosensory representation referred to as the body schema [1]. The almost century-old hypothesis that tool-use induces plastic changes resulting in the tool being incorporated in the body schema is nowadays widely accepted. Whether this somatosensory representation is truly modified remains unknown, however, as tool-use has never been shown to affect arm motor behaviour. Here we report that using a mechanical grabber that physically extends the arm does alter the kinematics of subsequent free-hand grasping movements. Remarkably, tool-use after-effects generalise to pointing movements, despite the absence of specific tool-training. Furthermore, this effect is driven by an increase of the represented length of the arm: after tool-use, subjects localised touches delivered on the elbow and middle fingertip of their arm as if they were farther apart. These findings indicate that tool-use alters the body schema, and also show that what is modified is the somatosensory representation of intrinsic properties of the body morphology.